Aáeáing the contribution of genebanks: the case of the UPM seed in Madrid - Gomez Campo, C.
(Es, En, Pt)
ilus., 312 ref.
Keywords: BANCO DE GENES; SEMILLAS; INVESTIGACION; ITALIA; NOTICIARIO DE RECURSOS FITOGENETICOS